AN ANALYSIS OF TRANSLATION TECHNIQUES BETWEEN AI AND HUMAN TRANSLATOR IN TRANSLATING CULTURAL WORDS IN THE GADIS KRETEK NOVEL - Sherly Adelia br Sembiring; Kammer Sipayung; Febrika Dwi Lestari (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study aims to analyze and compare the translation techniques used by Al and human translators in translating cultural words found in the Gadis Kretek novel. Using the observation method to collect data from the novel, this research applies Molina and Albir's (2002) translation techniques framework to examine the strategies employed by both translators. The finding of this research shows that 50 data fulfill thirteen types of translation technique. The findings reveal that Al translators employ 4 techniques in translating sentences containing cultural words: Adaptation, Literal Translation, Borrowing, and Calque. On the other hand, human translators utilize 8 techniques, including Establishing Equivalence, Adaptation, Description, Amplification, Modulation, Linguistic Amplification, Transposition, and Naturalization. The basic difference in translation techniques between Al translators and human translators lies in the range and variety of techniques they employ. Al translators only utilize 4 out of the 18 translation techniques proposed by Molina and Albir (2002), whereas human translators apply 8 techniques, making their approach more diverse and flexible. The result of this study is discrepancy in the number of techniques used can be attributed to several underlying reasons that stem from the fundamental differences in how Al and human translators process language, context, and culture. Among all the translation techniques analyzed, Al tends to use Literal Translation more frequently, Al translators most frequently use the Literal Translation technique (45 times), translating word-for-word from the source to the target language. This occurs because Al prioritizes lexical equivalence without considering cultural context, often resulting in unnatural or inaccurate translations. In contrast, human translators mostly use Adaptation (20 times) and Modulation (24 times). Adaptation replaces culture-specific terms with more familiar equivalents in the target culture, while Modulation adjusts the expression or point of view to sound more natural and contextually appropriate.